(Un)Covering Crisis: Using Canadian News Media to Understand Police Violence in Mental Health Responses to Indigenous People - Hey, Brandon; Ansloos, Jeffrey; Chowdhury, Mushfika; Heakes, Matthew (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2024)
Media depictions of Indigenous people have a long history of perpetuating racist, stereotyping, and victim blaming discourse. At the same time, recent scholarship asserts that news media is shifting its stance towards equity-groups involved in police-based mental health emergency response (MHER). Yet, few have sought to determine how these frames apply to police-based MHER for Indigenous people in Canada. Using an intersectional approach accounting for Indigeneity and mental illness, 168 Canadian media articles published between 1970 and 2022 were collated and analyzed using reflexive thematic analysis. Two overarching themes, affective realities and harms created by police involvement and normative practices perpetuating police impunity were found, as were several sub-themes. Implications for the role and function of news media in supporting the health and social policy needs of Indigenous groups are discussed.